Pola Sebaran Parameter Air Limbah (COD, BOD, dan Amonia) dari Kegiatan Eco Resort dan Wisata Bahari di Perairan Laut Flores - Raden Kokoh Haryo Putro; Rian Mei Kusuma Kusuma (Prosiding ESEC, 2023)
Wastewater generated from the operation of the Eco Resort and Marine Tourism activities originates from domestic activities. Wastewater from domestic activities is treated at the Sewage Treatment Plant (STP) and discharged into the sea. This research aims to provide a deeper understanding of the spatial distribution patterns of wastewater parameters (COD, BOD, and Ammonia) from Eco Resort and marine tourism activities in the Flores Sea. This study was conducted during the west season in January 2021, followed by modeling using MIKE 21 EcoLab, to determine the magnitude and distribution patterns of pollution in the Flores Sea. The modeling results show that outfall 3 significantly influences the increase in COD and BOD concentrations, especially during peak tide conditions and when the tide is receding. Another factor causing an increase in COD and BOD values is the proximity of the outfall to the wastewater discharge point. Based on the simulation results, the increase in ammonia concentration is influenced by environmental factors and tidal changes. During low tide conditions, the seawater current from the Flores Sea flows northward, transporting wastewater from outfalls 1 and 2 to the north, resulting in increased ammonia concentrations in that area.